Enseigner le genre épidictique - Sans, Benoît (Rivista Italiana di Filosofia del Linguaggio, 1970)
Since July 2013, my research team (GRAL, Université libre de Bruxelles) has started a new research that aims to reintroduce rhetorical training based on exercises inspired by the ancient practice in high schools and at University. In this paper, I consider the possibility of recreating a rhetorical teaching of the epideictic genre by reconstructing the technical knowledge that an ancient student acquired through epideictic training and by making some suggestions based on the ancient pedagogical material about the way we could teach epideictic to contemporary audiences.